The Lasting Influence of Dutch Colonialism on Language Use and Identity in Post-Colonial Indonesia - Elfa Salsabila; Aura Savinka; Asmyta Surbakti (Talenta Publisher, 2026)
This study qualitatively explores the enduring influence of Dutch colonialism on language use and identity in Indonesia. It finds that Dutch colonial administration created a hierarchical linguistic landscape where Dutch symbolized power and elite status, while Malay later formalized as Bahasa Indonesia was the widespread lingua franca that united the archipelago’s diverse ethnic groups. Colonial use of Malay, influenced by Dutch linguistic frameworks, facilitated the later rise of Indonesian as a national language embodying unity and resistance. The research highlights social stratification in language access, with Dutch limited to elites, shaping nationalist leadership. Furthermore, Dutch lexical and phonetic traces persist in Indonesian, reflecting a hybrid linguistic heritage. Post-independence nationalist efforts promoted Bahasa Indonesia to consolidate identity and reject colonial cultural dominance. The study demonstrates language;s dual role as a colonial tool and emancipatory resources, revealing the complexinterplay of domination, adaptation, and resistance in Indonesia’s post-colonial identity formation.